2011
DOI: 10.1016/j.geomorph.2011.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Classification and mapping of anthropogenic landforms on cultivated hillslopes using DEMs and soil thickness data — Example from the SW Parisian Basin, France

Abstract: Macaire. Classification and mapping of anthropogenic landforms on cultivated hillslopes using DEMs and soil thickness data -Example from the SW Parisian Basin, France. Geomorphology, Elsevier, 2011Elsevier, , 135 (1-2), pp.8-20. 10.1016Elsevier, /j.geomorph.2011 Classification and mapping of anthropogenic landforms on cultivated hillslopes using DEMs and soil thickness data -Example from the SW Parisian Basin, France AbstractThis study focuses on linear anthropogenic landforms of decametric width on cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
2
31
0
1
Order By: Relevance
“…Solum depth is strongly linked to landscape characteristics and it is important for soil mapping (Chartin et al, 2011), and land use planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…Solum depth is strongly linked to landscape characteristics and it is important for soil mapping (Chartin et al, 2011), and land use planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…Geostatistical models such as ordinary kriging (OK), regression kriging (RK), cokriging (COK), linear-nonlinear regression and few other multivariate methods were successfully tested in different landscapes for the soil depth estimation (Gessler et al 1995, Bourennane et al 2000, Tsai et al 2001, Henglet al 2004, Ziadat 2005, Kuriakose et al 2009, Chartin et al 2011. Topographic attributes derived from a digital elevation model (DEM) were used in these geostatistical models for the quantitative estimation of soil properties and their distribution (Gessler et al 1995, Boer et al 1996, Florinsky et al 2002, Thompson et al 2006, Pelletier and Rasmussen 2009, Vanwalleghem et al 2010, Mehnatkesh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term human activities such as cultivation and afforestation have a significant role in soil redistribution (Chartin et al 2011). Kuriakose et al (2009) compared different statistical methods to estimate soil thickness in the Western Ghats of Kerala state in India and found that RK is the best method for prediction, and land use was identified as the key explanatory variable for the soil depth estimation.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in Ethiopia, tillage erosion by simple tools, in addition to sediment transport due to water erosion, can lead to fast soil accumulation in the lynchets (Chartin et al, 2011;De Alba et al, 2004). As the rate of tillage erosion is independent from slope length, imposing lynchets can also develop on narrow parcels, established along the contour, as shown elsewhere (Patro et al, 2008).…”
Section: Formation Process Of Lynchetsmentioning
confidence: 89%
“…Occurrence in relation to farm-and woodland boundaries that are located along the contour (Szabó, 2010) and to land cultivation has been established rapidly (Aufrère, 1927;Raistrick and Chapman, 1929). Whereas for most soil scientists and geomorphologists (Chartin et al, 2011;Dabney et al, 1999;Ozer, 1969;Patro et al, 2008) there is no doubt that lynchets have grown as a consequence of tillage and water erosion, speculations on deliberate digging of terraces regularly surface (Fénelon, 1956;Fénelon, 1963;Raistrick and Chapman, 1929;Van Westreenen, 2008).…”
Section: Introductionmentioning
confidence: 99%